ANALISIS EFEKTIVITAS DAN KONTRIBUSI BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) KOTA PARIAMAN TAHUN 2017-2021 - Syofria Meidona; Juliandra Rahmat (IAIN BATUSANGKAR, 2023)
This study aims to determine and analyze the effectiveness and contribution of Land and Building Rights Acquisition Fees (BPHTB) taxes in Pariaman City. The research approach in the form of a descriptive approach is a research method used to examine existing facts systematically based on the object of research, existing facts to be collected and processed into data, then explained and drawn conclusions on data received from the Pariaman City Regional Financial and Revenue Management Agency in the form of target data and tax realization BPHTB Kota Pariaman. Data collection techniques used documentation and interviews. The data analysis technique used is a descriptive analysis technique. The results of this study are that during the 2017-2021 period the realization of BPHTB taxes has reached the desired target. The effectiveness of BPHTB tax collection in the last 5 years has reached the set target and BPHTB's tax contribution has increased in 2017 then decreased in 2018 and has increased again in 2019 and 2020 then decreased again in 2021. There are several factors that cause a decrease in BPHTB tax revenue, namely the lack of public awareness in increasing their land status rights to have a certificate, the Sales Value of Tax Objects (NJOP) in Kota Pariaman is still low when compared to the selling price of market prices, the lack of BPHTB tax sale and purchase transactions using certificates.